Final Report : Demonstrating Distributed Leadership through Cross-Disciplinary Peer Networks : Responding to Climate Change Complexity. - Davison, Aidan; Pharo, Emma; Warr, Kristin; Abuodha, Pamela; Boyd, Davina; Brown, Paul; Devereux, Peter; Egan, Anna; Hart, Gail; McGregor, Helen; Rooney, Millie; Terkes, Sarah (Australian Learning and Teaching Council, 2011)
Final report from the Leadership Networks for Climate Change (LNCC) project, which extended a successful pilot project at the University of Tasmania. Cross-disciplinary teaching networks were created at four universities using a 'communities of practice' approach. These networks advanced interdisciplinary teaching about climate change through peer collaboration. Networks cultivated distributed forms of leadership in addressing challenges stemming from two sources: first, disciplinary and administrative compartmentalisation within universities and, second, the real-world problems of climate change. The LNCC model relied upon two key network roles: that of the activator (or catalyst) and that of the integrator (or facilitator). The role of integrator was found to be vital to the success of the networks, particularly in addressing the heavy workloads of teaching staff. The integrator role offers significant returns in terms of cross- discipline collaboration for a modest investment and may also be a valuable model for academic developers in their efforts to increase engagement with teaching staff. The chief finding of the project was that LNCC model is highly adaptable to different institutional circumstances, with potential for creating systemic change within the sector. Distributed leadership development was found to be the key to maximising and maintaining this adaptability.